(untitled) (Contemporary Mathematics, 2025)
This paper is about the retrieval of gap dromions in presence of multiplicative white noise. The self-phase modulation structure is with cubic-quintic-septic-nonic structure. Two integration approaches retrieve the dromions and domain walls with the usage of the enhanced direct algebraic approach and the addendum to Kudryashov’s scheme. The solutions are subsequently classified.